Exploring the effects of knowledge on smoking: An analysis of adults in Malaysia - Cheah, Yong Kang; Lim, Hock Kuang; Mohd Yusoff, Muhammad Fadhli (2016)
In an effort to reduce the prevalence of smoking, the present study attempts to examine the factors that determine smoking. The present study uses two-tiered model to estimate the effects of demographic and knowledge factors on smoking participation and cigarette expenditure.As anticipated, knowledge is found to be negatively associated with an individual’s propensity to smoke.In addition, the findings suggest that age, gender, wealth index, education, ethnicity and house locality are significantly associated with smoking.In particular, males are more likely to smoke than females.Education reduces the likelihood of smoking.Urban dwellers tend to spend more on cigarette than rural dwellers.Policies directed toward reducing the prevalence of smoking may need to consider improving the knowledge of smoking among the adults.The policies must also be designed carefully to take into account of the demographic factors which are correlated with smoking.